Treatment of Severe Atopic Dermatitis with Dupilumab in Patients with Advanced Cancer - Tanczosova, Milena; Hugo, Jan; Gkalpakiotis, Spyridon (Journal of clinical medicine, 2023)
Atopic dermatitis is a chronic inflammatory intensively pruritic skin disease. Patients with moderate-to-severe atopic dermatitis or with difficult-to-treat areas are candidates for systemic therapy, especially when topical therapy is inadequate. Currently, we have available not only conventional immunosuppressive systemic therapy, but also targeted biological therapy, which has shown a remarkable reduction in clinical severity with a good safety profile. Dupilumab has been approved to treat moderate-to-severe atopic dermatitis. Even though the therapy has been available for more than 3 years, there are still limited data regarding the treatment of patients with concomitant cancer. Previous immunosuppressive treatment for atopic dermatitis, such as cyclosporine or azathioprine, poses a safety risk for patients with malignant disease. We present a case series of three patients with advanced cancer and severe atopic dermatitis treated with dupilumab for an average of 17 months with a great response toward atopic dermatitis without cancer recurrence. One patient had colorectal cancer' the second and the third both had cancer duplicity-colorectal and kidney cancer and penile squamous cell carcinoma with prostate cancer. Our cases suggest that dupilumab can safely control atopic dermatitis in patients with advanced cancer.
Keywords: cancer; dupilumab; real-world study; atopic dermatitis; biological therapy